Współczesne radio – pytanie o tożsamość - Wejs-Milewska, Violetta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
For over a decade now, we have been able to observe the increasing convergence of the media, thus leading to a unifying tendency in the forms of media message, a fusion of different styles and languages as well as of informational practices. The Internet plays more than a trifling role in this process, as thanks to its abilities both the untested and even the unknown are being equally explored. It seems that radio as an audio phenomenon of the 1930s is also undergoing this omnipresent tendency, losing its “original” [specifically its audio] identity. In the article, I raise the question of what chance radio has as a [traditional] audio medium in the context of ubiquitous stylistic multimedia unification.